A semi-solid electrolyte and its synthesis method and application, a semi-solid lithium battery
By using a semi -solid electrolyte composed of polymers, lithium salt, ionic liquid, inorganic fille, and fluoride amine solvents, the problem of poor hidden dangers and poor interface contact of liquid electrolytes in lithium batteries in lithium batteries are solved. Quick transmission and high ion conductive rates improve the safety performance of the battery.
Patent Information
- Application Number
- CN202310119870.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-02-16
AI Technical Summary
In existing lithium batteries, liquid electrolytes are flammable and explosive, and react with electrodes lead to safety hazards. The semi-solid electrolytes have poor contact, large impedance and low compatibility at the electrode interface, which affects the safety performance of the battery.
Adopt semi -solid electrolytes including polymers, lithium salt, ionic liquid, inorganic fille, and fluoride amine solvents, and accelerate the transmission rate of Li+through the high -agency constant and stability of fluoride amine solvents, increase the transmission rate of LI+, and increase the ion conductivity. And through the stable interface of fluoride chains to improve the safety of the battery.
The rapid transmission and high ionic conductivity of LI+in lithium batteries are realized, the electrochemical performance is optimized, and the lithium negative electrode is protected by stabilizing the interface to improve the safety performance of the battery.
Smart Images

Figure CN116014238B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium batteries, and in particular relates to a semi-solid electrolyte and a preparation method and application thereof, and a semi-solid lithium battery. Background Art
[0002] With the development of social economy, lithium batteries have been widely used in portable electronic products such as mobile phones, portable computers, camcorders, and cameras. Large-capacity lithium secondary batteries have been tried in electric vehicles and will become one of the main power sources of electric vehicles. With the continuous expansion of the application field of lithium secondary batteries, their safety performance becomes increasingly important.
[0003] Electrolyte is an important component of lithium-ion batteries, which plays the role of transmitting lithium ions and conducting current. At present, the electrolyte of commercial lithium batteries is mainly an organic carbonate system, which has defects such as easy leakage, flammability, explosion and volatility. At the same time, during the long cycle of lithium batteries, the electrolyte is easy to react with the active lithium metal negative electrode, continuously consume electrode materials and electrolyte, induce the formation of lithium dendrites, and react with the positive electrode to cause the continuous dissolution of transition metal ions or active substances, affecting the physicochemical properties of the negative electrode and electrolyte, and thus causing serious safety problems. Replacing flammable and explosive organic liquid electrolytes with non-flammable solid electrolytes is one of the effective ways to improve battery safety performance. Solid electrolytes have ultra-high mechanical strength and are believed to be able to effectively prevent the growth of lithium dendrites. However, there are problems such as poor interface contact, large interface impedance and low interface compatibility between electrodes and solid electrolytes. Therefore, considering the use of semi-solid electrolytes to improve the interface contact problem can largely solve the above problems.
[0004] At present, one of the methods for synthesizing semi-solid electrolytes is to immerse the solid electrolyte and absorb it in an organic carbonate electrolyte. However, this type of electrolyte is unstable to electrodes with strong oxidation / reduction properties, and is prone to side reactions and continuous consumption of the electrolyte. If the immersion amount is too much, some unfixed electrolyte will still remain on the component, which can easily pose a safety hazard during the battery cycle. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a semi-solid electrolyte and a preparation method and application thereof, and a semi-solid lithium battery. When the semi-solid electrolyte provided by the present invention is used in a lithium battery, Li + The transmission is faster, the ionic conductivity is higher, and the electrochemical performance is excellent.
[0006] In order to achieve the above objectives, the present invention provides the following technical solutions:
[0007] The invention provides a semi-solid electrolyte, which comprises a polymer, a lithium salt, an ionic liquid, an inorganic filler and a fluorinated amide solvent.
[0008] Preferably, the ionic liquid includes one or more of pyrrolidine ionic liquid, imidazole ionic liquid, bis(fluoromethanesulfonyl)imide and tetrafluoroboric acid.
[0009] Preferably, the fluorinated amide solvent includes one or more of 2,3,3,3-N,N-diethyl-tetrafluoropropionamide, 2,2,2-trifluoro-N,N-dimethylacetamide, 1,1,2,2-tetrafluoro-N,N-dimethylacetamide, 3,3,3-trifluoro-N,N-dimethylpropionamide and bistrifluoroacetamide.
[0010] Preferably, the polymer includes one or more of polyacrylonitrile, polyethylene oxide, polyvinylidene fluoride, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene, polyvinyl chloride and chlorinated polyethylene.
[0011] Preferably, the inorganic filler includes LiPON, Li 7 La 3 Nb 2 O 12 , Li 5 La 3 Ta 2 O 12 , Li 5 La 3 Zr 2 O 12 , Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 , Li 1.2 Al 0.2 Ti 1.8 (PO 4 ) 3 、LiZr 2 (PO 4 ) 3 , Li 0.34 La 0.51 TiO 2.94 , Li 0.38 La 0.56 Ti 0.99 Al 0.01 O 3 and Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 One or more of the .
[0012] Preferably, the mass of the inorganic filler is 10-60% of the mass of the semi-solid electrolyte.
[0013] Preferably, the mass of the polymer is 30-70% of the total mass of the fluorinated amide solvent and the ionic liquid.
[0014] The present invention also provides a method for preparing the semi-solid electrolyte, comprising the following steps:
[0015] The polymer, lithium salt, ionic liquid, inorganic filler and fluorinated amide solvent are mixed to obtain the semi-solid electrolyte.
[0016] The present invention also provides the use of the semi-solid electrolyte described above or the semi-solid electrolyte prepared by the above preparation method in a lithium battery.
[0017] The present invention also provides a semi-solid lithium battery, comprising a positive electrode, a negative electrode and a semi-solid electrolyte separator; the positive electrode comprises lithium iron phosphate, a ternary material or lithium nickel manganese oxide; the negative electrode is lithium or a lithium alloy; the material of the semi-solid electrolyte separator is the semi-solid electrolyte described above.
[0018] The present invention provides a semi-solid electrolyte, including a polymer, a lithium salt, an ionic liquid, an inorganic filler and a fluorinated amide solvent. The present invention selects a fluorinated amide solvent as a solvent in the semi-solid electrolyte. The fluorinated amide solvent has a high dielectric constant, high solubility in the polymer and the lithium salt, and does not react with the groups or ions in the polymer and the inorganic filler, which is conducive to accelerating the Li + The transmission rate of ion conductivity is improved. Moreover, fluorinated amide solvents not only have high thermal stability and chemical stability, but also the fluorine atoms in fluorinated amide solvents have a strong electron-withdrawing induction effect. The fluorinated chains can reduce the LUMO value, so that they are preferentially reduced and decomposed on the lithium negative electrode to generate some fluorinated intermediate phases, thereby stabilizing the interface semi-solid electrolyte film, protecting the lithium negative electrode, and improving the safety of the semi-solid electrolyte membrane. At the same time, ionic liquids are introduced into the semi-solid electrolyte of the present invention. The ionic liquids are liquid at room temperature and have the advantages of flame retardancy, lightning resistance, high boiling point and low volatility. At the same time, the ionic liquids have a wide electrochemical window and can be applied to lithium batteries in high-voltage systems. Although the ionic liquids have high viscosity, the fluorinated chains in the fluorinated amide solvents can reduce the interaction of hydrogen bonds, reduce the viscosity of the ionic liquids, and improve Li + transport capacity, thereby improving the ionic conductivity of the semi-solid electrolyte.
[0019] The present invention provides a method for preparing the semi-solid electrolyte, comprising the following steps: mixing a polymer, a lithium salt, an ionic liquid, an inorganic filler and a fluorinated amide solvent to obtain the semi-solid electrolyte. The present invention adopts a one-step mixing method to obtain the semi-solid electrolyte. Compared with other preparation methods, the preparation method provided by the present invention has simple steps, short time consumption, and is easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Graph showing the ionic conductivity of the semi-solid electrolyte of Comparative Example 1;
[0021] Figure 2 Graph showing the ionic conductivity of the semi-solid electrolyte of Example 1;
[0022] Figure 3 The charge and discharge curve of the semi-solid battery of comparative application example 1 at 0.1C;
[0023] Figure 4 This is a graph showing the cycle performance of the semi-solid-state battery of comparative application example 1;
[0024] Figure 5 The charge and discharge curve of the semi-solid battery of Application Example 1 at 0.1C;
[0025] Figure 6 This is a cycle performance diagram of the semi-solid-state battery of Application Example 1;
[0026] Figure 7 The charge and discharge curve of the semi-solid-state battery of Application Example 2 at 0.1C;
[0027] Figure 8 This is a cycle performance diagram of the semi-solid-state battery of Application Example 2;
[0028] Fig. 9 The charge and discharge curve of the semi-solid-state battery of Application Example 3 at 0.1C;
[0029] Fig.10 is a cycle performance diagram of the semi-solid-state battery of Application Example 3;
[0030] Fig.11 The charge and discharge curve of the semi-solid-state battery of Application Example 4 at 0.1C;
[0031] Fig.12 is a cycle performance diagram of the semi-solid-state battery of Application Example 4;
[0032] Fig.13 The charge and discharge curve of the semi-solid-state battery of Application Example 5 at 0.1C;
[0033] Fig.14 is a cycle performance diagram of the semi-solid-state battery of Application Example 5;
[0034] Fig.15 The charge and discharge curve of the semi-solid-state battery of Application Example 6 at 0.1C;
[0035] Fig.16 This is the cycle performance diagram of the semi-solid-state battery of Application Example 6. DETAILED DESCRIPTION
[0036] The invention provides a semi-solid electrolyte comprising a polymer, a lithium salt, an ionic liquid, an inorganic filler and a fluorinated amide solvent.
[0037] In the present invention, unless otherwise specified, the components are commercially available products well known to those skilled in the art.
[0038] In the present invention, the polymer preferably includes one or more of polyacrylonitrile, polyethylene oxide, polyvinylidene fluoride, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene, polyvinyl chloride and chlorinated polyethylene, and more preferably polyvinylidene fluoride-hexafluoropropylene. In the present invention, the weight average molecular weight of the polymer is preferably 400-500 g / mol, and more preferably 400-450 g / mol.
[0039] In the present invention, the fluorinated amide solvent preferably includes one or more of 2,3,3,3-N,N-diethyl-tetrafluoropropionamide, 2,2,2-trifluoro-N,N-dimethylacetamide, 1,1,2,2-tetrafluoro-N,N-dimethylacetamide, 3,3,3-trifluoro-N,N-dimethylpropionamide and bistrifluoroacetamide, more preferably 2,3,3,3-N,N-diethyl-tetrafluoropropionamide.
[0040] In the present invention, the ionic liquid preferably includes one or more of pyrrolidine ionic liquids, imidazole ionic liquids, bisfluoromethanesulfonimide and tetrafluoroboric acid; the pyrrolidine ionic liquid preferably includes N-alkyl-N-methylpyrrolidine; the imidazole ionic liquid preferably includes 1-vinyl-3-methylimidazole, 1-alkyl-3-methylimidazole bisfluoromethanesulfonimide, 1-alkyl-3-methylimidazole trifluoromethanesulfonimide. In the present invention, the alkyl group in the pyrrolidine ionic liquid preferably includes ethyl, propyl, butyl, hexyl or octyl, more preferably ethyl. The alkyl group in the imidazole ionic liquid preferably includes methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, dodecyl, tetradecyl, hexadecyl or octadecyl, more preferably methyl or ethyl.
[0041] In the present invention, the lithium salt preferably includes LiTFSI, LiFSI, LiBOB, LiDFOB and LiPF 6 One or more of the above, preferably LiTFSI or LiBOB.
[0042] In the present invention, the inorganic filler preferably includes LiPON, Li 7 La 3 Nb 2 O 12 , Li 5 La 3 Ta 2 O 12 , Li5 La 3 Zr 2 O 12 , Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 , Li 1.2 Al 0.2 Ti 1.8 (PO 4 ) 3 、LiZr 2 (PO 4 ) 3 , Li 0.34 La 0.51 TiO 2.94 , Li 0.38 La 0.56 Ti 0.99 Al 0.01 O 3 and Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 One or more of the following, more preferably Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 .
[0043] In the present invention, the mass of the polymer is preferably 30-70% of the total mass of the fluorinated amide solvent and the ionic liquid, and more preferably 40-50%. In the present invention, the mass ratio of the fluorinated amide solvent to the ionic liquid is preferably 1:1-1:5, and more preferably 1:2-1:4. In the present invention, the concentration of the lithium salt in the semi-solid electrolyte is preferably 0.5-5M, and more preferably 1-4M. In the present invention, the mass of the inorganic filler is preferably 10-60% of the mass of the semi-solid electrolyte, and more preferably 40-50%.
[0044] The present invention also provides a method for preparing the semi-solid electrolyte, comprising the following steps:
[0045] The polymer, lithium salt, ionic liquid, inorganic filler and fluorinated amide solvent are mixed to obtain the semi-solid electrolyte.
[0046] In the present invention, the mixing is preferably a first mixing of the polymer, the lithium salt, the ionic liquid and the fluorinated amide solvent, and a second mixing of the obtained mixture and the inorganic filler.
[0047] In the present invention, the first mixing method is preferably magnetic stirring, the rotation speed of the magnetic stirring is preferably 100 to 200 rpm, more preferably 100 to 150 rpm, and the time is preferably 4 to 10 hours, more preferably 5 to 8 hours.
[0048] In the present invention, the second mixing method is preferably magnetic stirring, the rotation speed of the magnetic stirring is preferably 800 to 1200 rpm, more preferably 900 to 1000 rpm, and the time is preferably 2 to 6 hours, more preferably 3 to 5 hours.
[0049] The present invention also provides application of the above-mentioned semi-solid electrolyte in a lithium battery.
[0050] The present invention provides a semi-solid lithium battery, comprising a positive electrode, a negative electrode and a semi-solid electrolyte separator;
[0051] The positive electrode preferably includes lithium iron phosphate, a ternary material or lithium nickel manganese oxide; the ternary material preferably includes NMC622.
[0052] The negative electrode is preferably lithium or a lithium alloy, more preferably lithium; the lithium alloy preferably includes a lithium-manganese alloy, a lithium-boron alloy, a lithium-aluminum alloy or a lithium-indium alloy, more preferably a lithium-manganese alloy.
[0053] In the present invention, the material of the semi-solid electrolyte separator is the semi-solid electrolyte described above. In the present invention, the thickness of the semi-solid electrolyte separator is preferably 40 to 100 μm, more preferably 50 to 80 μm.
[0054] In the present invention, the preparation of the semi-solid electrolyte membrane preferably includes hot pressing the semi-solid electrolyte into a film to obtain the semi-solid electrolyte membrane.
[0055] In the present invention, the conditions for hot pressing film forming preferably include: the temperature is preferably 60-150°C, more preferably 120-130°C, the pressure is preferably 600-1000Pa, more preferably 800-900Pa, and the time is preferably 3-5min, more preferably 4-5min.
[0056] The lithium ion battery composite gel separator provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0057] Example 1
[0058] The polymer PVDF-HFP, ionic liquid EMIMTFSI and lithium salt LiTFSI were dissolved in 2,2,2-trifluoro-N,N-dimethylacetamide and magnetically stirred for 5 h. Then, the inorganic filler (Li 6.4 La3 Zr 1.4 Ta 0.6 O 12 ) was added thereto and magnetically stirred for 5 h to obtain a semi-solid electrolyte;
[0059] In the above-mentioned semi-solid electrolyte: the volume ratio of 2,2,2-trifluoro-N,N-dimethylacetamide and ionic liquid is 1:1; the mass of the polymer is 40% of the total mass of the 2,2,2-trifluoro-N,N-dimethylacetamide solvent and the ionic liquid; the concentration of the lithium salt in the semi-solid electrolyte is 1M; the mass concentration of the inorganic filler in the semi-solid electrolyte is 40%.
[0060] Example 2
[0061] The only difference from Example 1 is that 2,2,2-trifluoro-N,N-dimethylacetamide is replaced by 2,3,3,3-N,N-diethyl-tetrafluoropropionamide.
[0062] Example 3
[0063] The only difference from Example 1 is that LiTFSI is replaced by LiBOB.
[0064] Example 4
[0065] The only difference from Example 1 is that the mass concentration of the inorganic filler in the semi-solid electrolyte is 10%.
[0066] Example 5
[0067] The only difference from Example 1 is that the mass concentration of the inorganic filler in the semi-solid electrolyte is 60%.
[0068] Example 6
[0069] The only difference from Example 1 is that the concentration of LiTFSI in the semi-solid electrolyte is 3M.
[0070] Comparative Example 1
[0071] The only difference from Example 1 is that 2,2,2-trifluoro-N,N-dimethylacetamide is replaced by acetone.
[0072] Application Example 1
[0073] The semi-solid electrolyte prepared in Example 1 was hot-pressed at 120° C. and 800 Pa for 4 min to form a film, thereby obtaining a semi-solid electrolyte membrane;
[0074] The semi-solid electrolyte separator was cut into small discs with a diameter of 16 mm, and assembled with the positive electrode material NMC622 and the negative electrode material Li metal to form an NMC622 / semi-solid electrolyte / Li full battery.
[0075] Application Example 2
[0076] The semi-solid electrolyte prepared in Example 2 was hot-pressed at 100° C. and 1000 Pa for 4 min to form a film, thereby obtaining a semi-solid electrolyte membrane;
[0077] The semi-solid electrolyte separator was cut into small discs with a diameter of 16 mm, and assembled with the positive electrode material NMC622 and the negative electrode material Li metal to form an NMC622 / semi-solid electrolyte / Li full battery.
[0078] Application Example 3
[0079] The semi-solid electrolyte prepared in Example 3 was hot-pressed at 120° C. and 600 Pa for 5 min to form a film, thereby obtaining a semi-solid electrolyte membrane.
[0080] The semi-solid electrolyte separator was cut into small discs with a diameter of 16 mm, and assembled with the positive electrode material NMC622 and the negative electrode material Li metal to form an NMC622 / semi-solid electrolyte / Li full battery.
[0081] Application Example 4
[0082] The semi-solid electrolyte prepared in Example 4 was hot-pressed at 150° C. and 800 Pa for 3 min to form a film, thereby obtaining a semi-solid electrolyte membrane.
[0083] The semi-solid electrolyte separator was cut into small discs with a diameter of 16 mm, and assembled with the positive electrode material NMC622 and the negative electrode material Li metal to form an NMC622 / semi-solid electrolyte / Li full battery.
[0084] Application Example 5
[0085] The semi-solid electrolyte prepared in Example 5 was hot-pressed at 80° C. and 800 Pa for 5 min to form a film, thereby obtaining a semi-solid electrolyte membrane.
[0086] The semi-solid electrolyte separator was cut into small discs with a diameter of 16 mm, and assembled with the positive electrode material NMC622 and the negative electrode material Li metal to form an NMC622 / semi-solid electrolyte / Li full battery.
[0087] Application Example 6
[0088] The semi-solid electrolyte prepared in Example 6 was hot-pressed at 80° C. and 1000 Pa for 4 min to form a film, thereby obtaining a semi-solid electrolyte membrane.
[0089] The semi-solid electrolyte separator was cut into small discs with a diameter of 16 mm, and assembled with the positive electrode material NMC622 and the negative electrode material Li metal to form an NMC622 / semi-solid electrolyte / Li full battery.
[0090] Comparative application example 1
[0091] The semi-solid electrolyte prepared in Comparative Application Example 1 was hot-pressed for 4 minutes under the conditions of 60° C. and 800 Pa to obtain a semi-solid electrolyte separator;
[0092] The semi-solid electrolyte separator was cut into small discs with a diameter of 16 mm, and assembled with the positive electrode material NMC622 and the negative electrode material Li metal to form an NMC622 / semi-solid electrolyte / Li full battery.
[0093] Test example:
[0094] Ionic conductivity test:
[0095] The room temperature ionic conductivity of the semi-solid electrolytes prepared in Comparative Example 1 and Example 1 was tested, and the test results are shown in Figures 1-2 ,from Figures 1-2 It can be seen that the conductivity of Comparative Example 1 is 5*10 -5 S / cm, the conductivity of Example 1 is 4.4*10 -4 S / cm, a difference of one order of magnitude.
[0096] Charge and discharge performance test:
[0097] The present invention tests the charge-discharge performance and cycle performance of the NMC622 / semi-solid electrolyte / Li full battery prepared in Comparative Application Example 1 and Application Examples 1 to 6. The test results are shown in Table 1. Figures 3 to 16 ,in, Figures 3-4 The charge and discharge curves and cycle performance test diagrams of the semi-solid-state battery of comparative application example 1 at 0.1C are shown in FIG. Figures 3-4 It can be seen that the semi-solid-state battery prepared in Comparative Application Example 1 has an initial discharge capacity of 98 mAh / g. After 38 cycles, the capacity is only 87 mAh / g, and the capacity retention rate is 88.6%.
[0098] Figures 5-6 They are respectively the charge and discharge curves and cycle performance test diagrams of the semi-solid-state battery of Application Example 1 at 0.1C. Figures 5-6 It can be seen that the semi-solid-state battery prepared in Application Example 1 has an initial discharge capacity of 122 mAh / g, which reaches 131 mAh / g after 5 cycles of activation, and a discharge capacity of 117 mAh / g after 70 cycles, with a capacity retention rate of 92.9%.
[0099] Figures 7-8 They are respectively the charge and discharge curves and cycle performance test diagrams of the semi-solid-state battery of Application Example 2 at 0.1C. Figures 7-8It can be seen that the semi-solid-state battery prepared in Application Example 2 has an initial discharge specific capacity of 157 mAh / g, a capacity of 139 mAh / g after 90 cycles, and a capacity retention rate of 88.5%.
[0100] Figures 9-10 The charge and discharge curves of the semi-solid-state battery of Application Example 3 at 0.1C are as follows: Figures 9-10 It can be seen that the battery assembled with the semi-solid electrolyte prepared in Application Example 3 has an initial discharge capacity of 143 mAh / g, a capacity of 135 mAh / g after 60 cycles, and a capacity retention rate of 94.4%.
[0101] Figures 11-12 They are the charge and discharge curves of the semi-solid-state battery of Application Example 4 at 0.1C. Figures 11-12 It can be seen that the semi-solid-state battery prepared in Application Example 4 has an initial discharge specific capacity of 121 mAh / g, a capacity of 113 mAh / g after 80 cycles, and a capacity retention rate of 93.4%.
[0102] Figures 13-14 They are the charge and discharge curves of the semi-solid-state battery of Application Example 5 at 0.1C. Figures 13-14 It can be seen that the semi-solid-state battery prepared in Application Example 5 has an initial discharge specific capacity of 130 mAh / g, a capacity of 126 mAh / g after 60 cycles, and a capacity retention rate of 96.9%.
[0103] Figures 15-16 They are the charge and discharge curves of the semi-solid-state battery of Application Example 6 at 0.1C. Figures 15-16 It can be seen that the semi-solid-state battery prepared in Application Example 6 has an initial discharge specific capacity of 145 mAh / g, a capacity of 128 mAh / g after 90 cycles, and a capacity retention rate of 88.3%.
[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A semi-solid electrolyte, characterized in that: The semi-solid electrolyte comprises a polymer, a lithium salt, an ionic liquid, an inorganic filler and a fluorinated amide solvent, and is divided into a first semi-solid electrolyte, a second semi-solid electrolyte, a third semi-solid electrolyte and a fourth semi-solid electrolyte; In the first semi-solid electrolyte, the polymer is polyvinylidene fluoride-hexafluoropropylene, the ionic liquid is EMIMTFSI, the lithium salt is LiBOB, and the inorganic filler is Li 6.4 LqCy 1.4 Ta 0.6 O 12 1. The fluorinated amide solvent is 2,2,2-trifluoro-N,N-dimethylacetamide, and the volume ratio of 2,2,2-trifluoro-N,N-dimethylacetamide to the ionic liquid is 1:1; the mass of the polymer is 40% of the total mass of the 2,2,2-trifluoro-N,N-dimethylacetamide solvent and the ionic liquid; the concentration of the lithium salt in the semi-solid electrolyte is 1M; the mass concentration of the inorganic filler in the semi-solid electrolyte is 40%; In the second semi-solid electrolyte, the polymer is polyvinylidene fluoride-hexafluoropropylene, the ionic liquid is EMIMTFSI, the lithium salt is LiTFSI, and the inorganic filler is Li 6.4 LqCy 1.4 Ta 0.6 O 12 1. The fluorinated amide solvent is 2,2,2-trifluoro-N,N-dimethylacetamide, and the volume ratio of 2,2,2-trifluoro-N,N-dimethylacetamide to the ionic liquid is 1:1; the mass of the polymer is 40% of the total mass of the 2,2,2-trifluoro-N,N-dimethylacetamide solvent and the ionic liquid; the concentration of the lithium salt in the semi-solid electrolyte is 1M; the mass concentration of the inorganic filler in the semi-solid electrolyte is 10%; In the third semi-solid electrolyte, the polymer is polyvinylidene fluoride-hexafluoropropylene, the ionic liquid is EMIMTFSI, the lithium salt is LiTFSI, and the inorganic filler is Li 6.4 LqCy 1.4 Ta 0.6 O 12 1. The fluorinated amide solvent is 2,2,2-trifluoro-N,N-dimethylacetamide, and the volume ratio of 2,2,2-trifluoro-N,N-dimethylacetamide to the ionic liquid is 1:1; the mass of the polymer is 40% of the total mass of the 2,2,2-trifluoro-N,N-dimethylacetamide solvent and the ionic liquid; the concentration of the lithium salt in the semi-solid electrolyte is 1M; the mass concentration of the inorganic filler in the semi-solid electrolyte is 60%; In the fourth semi-solid electrolyte, the polymer is polyvinylidene fluoride-hexafluoropropylene, the ionic liquid is EMIMTFSI, the lithium salt is LiTFSI, and the inorganic filler is Li 6.4 LqCy 1.4 Ta 0.6 O 12 1. The fluorinated amide solvent is 2,2,2-trifluoro-N,N-dimethylacetamide, and the volume ratio of 2,2,2-trifluoro-N,N-dimethylacetamide to the ionic liquid is 1:1; the mass of the polymer is 40% of the total mass of the 2,2,2-trifluoro-N,N-dimethylacetamide solvent and the ionic liquid; the concentration of the lithium salt in the semi-solid electrolyte is 3M; the mass concentration of the inorganic filler in the semi-solid electrolyte is 40%; The method for preparing the semi-solid electrolyte comprises the following steps: The polymer, lithium salt, ionic liquid, inorganic filler and fluorinated amide solvent are mixed to obtain the semi-solid electrolyte.
2. The method for preparing the semi-solid electrolyte according to claim 1, characterized in that: The following steps are involved: The polymer, lithium salt, ionic liquid, inorganic filler and fluorinated amide solvent are mixed to obtain the semi-solid electrolyte.
3. Use of the semi-solid electrolyte according to claim 1 or the semi-solid electrolyte prepared by the preparation method according to claim 2 in a lithium battery.
4. A semi-solid lithium battery, characterized in that: including a positive electrode, a negative electrode and a semi-solid electrolyte separator; The positive electrode comprises lithium iron phosphate, ternary material or lithium nickel manganese oxide; the negative electrode is lithium or lithium alloy; the material of the semi-solid electrolyte separator is the semi-solid electrolyte described in claim 1.
Citation Information
Patent Citations
Electrolyte for lithium ion battery
CN106848398A
Inorganic ceramic ion conductor-based composite solid electrolyte film and preparation method thereof
CN114447405A